Centripetalism and Electoral Moderation in Established Democracies. Issue 2 (3rd April 2018) - Reilly, Benjamin
Abstract : Centripetal approaches to ethnic conflict management seek to promote inter-ethnic accommodation and moderation by making politicians dependent on the electoral support of groups other than their own base. There is an ongoing debate about the utility of such approaches, including which kinds of electoral systems can best promote moderate and centrist politics in deeply divided societies. Neglected in this debate, however, has been the experience of ethnically diverse established democracies utilizing centripetal electoral models. This article examines historical evidence from Australia, and recent natural experiments with subnational electoral reform in the United States, which lend support to centripetal claims that preferential, "ranked choice" or "instant runoff" voting can encourage electoral moderation and address political polarization.